Making a HIIT: co-design of high-intensity interval training workouts with students & teachers within the curriculum - Stephanie L. Duncombe; Alan R. Barker; Lisa Price; Jacqueline L. Walker; Yong Liu; Dewi Paris; Michalis Stylianou (BMC, 2023)
Abstract Background High-intensity interval training (HIIT) interventions are becoming more common in schools. However, limited input has been sought from end-users, which can help design interventions that are more engaging and context appropriate, therefore increasing their potential for successful implementation. One method of engaging end-users is co-design, which involves an active collaboration to design solutions to pre-specified problems. This paper aimed to: (1) describe the methodology and results of the co-design process in Making a HIIT to develop HIIT workouts for a school-based intervention; and (2) evaluate the feasibility and impact of co-designing HIIT workouts with students and teachers within the health and physical education (HPE) curriculum. Methods The development of the HIIT workouts occurred during obligatory HPE lessons with year seven and eight students. The co-design process included: (1) identifying barriers and facilitators to exercise to create evaluation criteria for creating the HIIT workouts; (2) exploring HIIT; (3) defining HIIT parameters (intensity and interval length); (4) creating HIIT workouts using the parameters and evaluation criteria; (5) trialling and modifying the HIIT workouts based on class feedback and intensity data. To evaluate the feasibility and impact of the co-design process, a thematic analysis was completed using teacher interviews, student discussions, and student surveys. Results Five classes comprised of 121 students (12-14 years; 49% female) and five teachers were involved in the co-design process across three schools in Queensland, Australia. A total of 33 HIIT workouts were created aimed at satisfying the HIIT parameters and variations of the following evaluation criteria: (1) fun; (2) social; (3) achievable skill level; (4) feeling accomplished; and (5) beneficial for health. From the thematic analysis, three themes (acceptability; implementation; integration) and 12 codes contributed to the overarching understanding of the feasibility of the lessons within the curriculum and a further three themes (perceived changes to lessons; educative outcomes; personal and social capabilities) and three codes contributed towards understanding their impact. Conclusion Overall, co-designing HIIT workouts was feasible within the HPE curriculum and may have contributed to positive educative outcomes. Using this methodology could improve the implementation of HIIT interventions within HPE while supporting educative benefits.